‘Senior Nursing Students and Interns’ Concerns and Willingness to Treat Patients with COVID-19: A Strategy to Expand National Nursing Workforce during the COVID-19 Pandemic - Alshutwi SS (Dove Medical Press, 2021)
Sitah S Alshutwi1,2 1College of Nursing, King Saud Bin Abdulaziz University for Health Sciences, Riyadh City, Saudi Arabia; 2King Abdullah International Medical Research Center, Riyadh City, Saudi ArabiaCorrespondence: Sitah S Alshutwi Email Shutwis@ksau-hs.edu.saBackground: The coronavirus disease of 2019 (COVID-19) pandemic has challenged the existing healthcare delivery systems worldwide and overwhelmed the globally short healthcare workforce, particularly nurses. Nurses are recognized as front-line responders to the COVID-19 pandemic and are crucial healthcare members to win the fight against the evolving COVID-19. Considering the long-lasting shortage of national nurses, and turnover of the current nursing workforce, it is essential to consider unconventional strategies aiming at expanding the national nursing workforce in order to embrace the impact of COVID-19.Objective: This study aimed to measure senior nursing students and intern’s willingness to treat patients with COVID-19. Further, this study investigated their feelings, knowledge, and concerns regarding treating patients with COVID-19.Methods: This quantitative, cross-sectional study utilized self-reported survey gathered from a convenience sample of 178 senior nursing students and interns. A 7-item scale was used to measure the participants’ willingness to treat patients with COVID-19. The data were collected between March 2020 and April 2020.Results: Out of 178 participants, 50.56% were at Level 8, 89.33% were single, and 53.37% had a very satisfactory grade point average. The highest proportion of the respondents (38.20%) felt neutral about treating patient with COVID-19, while 53.93% had good knowledge about COVID-19. The perceived willingness to treat of participants had an overall mean score of 20.19, which indicated neutral willingness to treat patients with COVID-19. Participants’ feelings about treating patients with COVID-19 predicted their willingness to treat patients with COVID-19 (P< 0.001).Conclusion/Recommendation: There is a clear need for educational and training programs both in clinical practice and academia for the improvement among nursing students and interns who reported paucity of knowledge about COVID-19. Furthermore, hospital institutions should provide additional incentives or hazard protections to maintain and even increase the number of staff at the frontline who are willing to care for patients amid the deadly pandemic of COVID-19.Keywords: COVID-19, nursing interns, nursing students, willingness to treat